Facultative Anaerobic Bacterial Profile of Bacteremia and Septicemia among ICU Patients and its Antibiotic Susceptibility Pattern in Central Nepal - Jha, Brajesh Kumar; Mahaseth, Suryanarayan; Sanjana, Rajkumari (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Bacteremia and septicemia is a life threatening condition resulting in major cause of morbidity and mortality in patients. The aim of this study was to determine prevalence of bacteremia and septicemia among surgical ICU patients and its antibiotic susceptibility pattern. Methods: A cross-sectional study was carried out among the suspected cases from surgical ICUs of COMS-TH from July 2017 to December 2020. Blood samples were collected, processed, isolated and identified according to standard methodology. Multidrug resistance in Gram negative bacterial (MDR) and methicillin resistant S.aureus (MRSA) screening was done by following the standard protocol. Results: A total number of 450 samples were processed, 48(10.7%) bacterial isolates from patients’ blood sample showed positive by culture from department of surgical ICUs, College of Medical Sciences Teaching Hospital, Nepal. This study showed more incidences of gram negative isolates which are responsible for septicemia as compared to gram positive isolates. Most frequently used drugs like Ciprofloxacin (83.9%), Gentamycin (74.2%), Ceftrixone and Ampicillin (71.0%), Cefazolin and Chloramphenicol (67.7%), Ofloxacin (67.7%), Amikacin (64.5%), Amoxyclave (61.3%), showed high rate of resistance among the isolates. Cefotaxime and Co-Trimoxazole (58.1%) showed second highest resistance pattern among GNB isolates from ICU patients. The least resistance pattern among the GPC was found in drugs like Amikacin and Azithromycin (47.1%) and Vancomycin (35.3%) Meropenem (29.4%). Coagulase negative Staphylococcus (CONS) had shown MDR 66.6% showed highest resistance pattern among Enterococcus spp, CoNS and S.aureus. This indicates most of the organisms were either moving towards resistance or already acquired resistance against antibiotics. Conclusions : Blood culture positive rate of the isolates from surgical ICUs of COMS-TH was 48(10.7%) of the total 450 samples. Pseudomonas aeruginosa and S.aureus were most common pathogen causing bacteremia and septicemia. None of the antibiotics were 100% sensitive for P.aeruginosa, even Meropenem showed reduced sensitivity. Among all antibiotics Ampicillin and Amikacin followed by Ciprofloxacin has lowest sensitivity towards the organisms.